Archives and Museums for Reconciliation and Peacebuilding in Timor-Leste | UNESCO - Unesco (Unesco, 2023)
On 10 August 2023, UNESCO organized a National Stakeholders’ Meeting on Conflict Reconciliation and Peacebuilding in Timor-Leste, with a focus on the role of archives and alternative sites for history and peace education in the country.
Keywords: 2023-08 August